Exceptional thermal stability of undoped anatase TiO2 photocatalysts prepared by a solvent-exchange method1. Issue 46 (23rd May 2015) - Krivtsov, Igor; Ilkaeva, Marina; Avdin, Viacheslav; Amghouz, Zakariae; Khainakov, Sergei A.; García, José R.; Díaz, Eva; Ordóñez, Salvador
<x xml:space="preserve">Abstract</x> A new solvent-exchange method for preparation of undoped anatase TiO2 nanoparticles with unprecedented thermal stability has been presented.